2020
DOI: 10.1007/s42452-020-2537-2
|View full text |Cite
|
Sign up to set email alerts
|

Photo-assisted mineralisation of titan yellow dye using ZnO nanorods synthesised via environmental benign route

Abstract: Green synthesis of metal oxide nanoparticles using plant extract is a most promising substitute for regular methods that involve chemical synthesis approach. The present study reports the synthesis of ZnO nano rods (ZNRs) using Calotropis gigantea, a plant rich in flavonoids and alkaloids and their application as a photocatalyst in the degradation of titan yellow dye. The synthesized ZNRs were characterized using XRD, FESEM-EDS and HRTEM-SAED. The XRD results confirm the formation of wurtzite ZnO. The FESEM im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…ZnO nanorods synthesized using sustainable pathways were also investigated for photocatalytic activity by Vidya et al [66]. For the green synthesis, Calotropis gigantea leaf extract was used, which was prepared as follows: Firstly, the collected leaves were washed and dried in sun; after that 50 g of them was cut into small pieces and mixed with 500 mL of distilled water.…”
Section: Green Synthesis Of Special Nanomaterials Based On Tio 2 and Znomentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO nanorods synthesized using sustainable pathways were also investigated for photocatalytic activity by Vidya et al [66]. For the green synthesis, Calotropis gigantea leaf extract was used, which was prepared as follows: Firstly, the collected leaves were washed and dried in sun; after that 50 g of them was cut into small pieces and mixed with 500 mL of distilled water.…”
Section: Green Synthesis Of Special Nanomaterials Based On Tio 2 and Znomentioning
confidence: 99%
“…For the synthesis of ZnO nanorods, 100 mL of the leaf extract was firstly boiled and stirred at 60-80 • C, and when the extract reached 80 • C, 5 g of zinc nitrate hexahydrate (Zn(NO) 3 •6(H 2 O)) was added and boiled until a deep yellow paste appeared. Finally, this paste was then calcined at 400 • C for 1 h. For the characterization, various techniques were used, such as XRD, SEM, TEM, EDS, FTIR and UV-Vis spectrometry [66]. XRD results proved the wurtzite structure of ZnO as well as the presence of some impurities.…”
Section: Green Synthesis Of Special Nanomaterials Based On Tio 2 and Znomentioning
confidence: 99%
“…Environment friendly approaches for synthesis of ZnO and TiO 2 nanostructures have been one of the focus areas of the research. For example, green synthesis methods such as hydrothermal route utilizing Prunus cerasifera leaf, [ 239 ] calcination of broccoli extract, [ 240 ] using water extract of Calotropis gigantea leaves, [ 241 ] application of Carissa edulis as the capping agent for the preparation of ZnO nanostructures [ 242 ] have been reported recently. Immobilization of such nanostructures is necessary for environment friendly applications of ZnO and TiO 2.…”
Section: Photocatalysis Related Applications In Uv Sensingmentioning
confidence: 99%
“…The present CoONPs shows 92.20% DE of MX at neutral pH with visible light irradiation indicates faster degradation rate. On the flipside, most of the reported conventional catalysts for the degradation of TY are TiO 2 or ZnO based nanoparticles induced by UV light [46][47][48] . Recently, Pal et al [45] have reported an efficient photocatalyst, ZnO nano particles synthesized by using Moringa Oleifera leaf extract which degrades TY about 96.0% under 60 min visible light irradiation in the pH range 2.0-12.0.…”
Section: Photocatalytic Degradation Study Of Murexide and Titan Yellomentioning
confidence: 99%